Visual Communication and Design’s Role Drives Branding Innovation and Social Responsibility - Stephen T.F. Poon (ITB Journal Publisher, LPPM ITB, 2016)
In this paper, the aim of research is to analyse the theoretical principles of traditional and newer forms of branding design, and to review the visual communicator’s roles as constructed through traditional, social and postmodernist perspectives. Where designers traditionally direct their course in the branding process to solving clients’ problems through the production of symbolic icons and images, this study will place their responsibility towards understanding society’s attitudinal and behavioural change at the forefront. This paper uses case study and qualitative inquiry methods to challenge the design fraternity to see beyond the bread-and-butter work behind conceptual design development, and to find a stronger relational understanding between their life experiences, changing consumer perceptions of the world, and businesses’ ultimate goals of profit. Research shows that as the dynamics of ethical business and social purpose continue to affect the production and consumption of goods, the visual communicator’s role is to both define and empower cultural consumption as the core brand purpose of today’s organisations - five decades since Ken Garland’s manifesto; “First Things First” was proclaimed. Lastly, it shall be argued for every designer to evaluate their social responsibility in the branding execution of marketed consumer brands beyond symbolic meaning construction. Keywords: design; postmodern branding; social innovation; social purpose.